Предмет: Алгебра,
автор: khankarolina
Помогите решить даю 50 баллов.
6b/a^2-b^2 + 3/b-a - 4/a+b при a = -2 b = 3
Приложения:
Ответы
Автор ответа:
0
6b/a^2-b^2 + 3/b-a - 4/a+b = 6b/(a-b)(a+b) + 3/b-a - 4/a+b = 6b/(-2-3)(-2+3) + 3/(3+2) - 4/(-2+3) = 6b/-5 + 3/5 - 4/1 = 6*3/-5 + 3/5 - 4 = -18/5 + 3/5 - 4 = -15/5 - 4 = - 3 - 4 = -7
Ответ: -7
Автор ответа:
0
Ответ:
-7
Объяснение:
6b/a^2-b^2 + 3/b-a - 4/a+b
6*3/((-2)^2-3^2) + 3/(3-(-2)) - 4/(-2+3)
18/(4-9) + 3/(3+2) - 4/(-2+3)
18/-5 + 3/5 - 4/1
18/-5 + 3/5 - 4
- (18/5) + 3/5 - 4
(-18+3)/5 - 4
-15/5 - 4
-3-4
-7
Похожие вопросы
Предмет: Русский язык,
автор: brain2014
Предмет: Английский язык,
автор: арпин
Предмет: Английский язык,
автор: qyvin10
Предмет: Математика,
автор: 8Ytzerd8
Предмет: Алгебра,
автор: Mognolia